Making democratic theory democratic : democracy, law, and administration after Weber and Kelsen - Turner, Stephen P., 1951-; Mazur, George (New York, NY : Routledge, 2023)
This book addressees a timely and fundamental problematic: the gap between the aims that people attempt to realize democratically and the law and administrative practices that actually result. The chapters explain the realities that administration poses for democratic theory. Topics include the political value of accountability, the antinomic character of political values, the relation between ultimate ends and the intermediate ends that are sought by constitutions, and a reconsideration of the meaning of the rule of law itself. The essays are inspired by the demystifying realism of Max Weber and Hans Kelsen, including explications of their views on law, constitutions, and the rule of law. The book will be of interest to social and political theorists, philosophers of law, and legal theorists, and for discussions of democratic theory, the administrative state, constitutionalism, and justice, as well as to readers of Weber and Kelsen.
5 Religious Pluralism, Toleration, and Liberal Democracy: Past, Present, and Future -- 6 The End of Clear Lines: Academic Freedom and Administrative Law -- PART II Fundamental Political Theory -- 7 The Method of Antinomies: Oakeshott and Others -- 8 Decisionism and Politics: Weber as Constitutional Theorist -- 9 The Rule of Law Deflated: Weber and Kelsen -- Acknowledgments -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Democracy; POLITICAL SCIENCE / Political Process / General; POLITICAL SCIENCE / Public Affairs & Administration